Using Municipal Tourism Assets for Leveraging Local Economic Development in South Africa - Rogerson Christian M. (Bulletin of Geography. Socio-Economic Series)
Tourism development can be a vital component of place-based development initiatives in the global South. The nexus of tourism and place-based development thinking in the global South and of the role of local governments is only beginning to be investigated by tourism scholars. This article explores the record of using tourism assets in one South African local municipality for leveraging local economic development. Evidence is drawn from the experience of the King Sabata Dalindyebo Local Municipality in South Africa's Eastern Cape province. The research results point to an unimpressive record on the part of local government in directing the use of local assets for assisting tourism development. Several challenges are revealed to explain the underperformance of potentially valuable local assets in this municipality. Institutional and governance shortcomings, including widespread corruption, underpin the observed weaknesses both in the everyday workings of local government in relation to service delivery and infrastructure support as well as its inability to implement plans for local economic development. Well-meaning policies proposed for tourism development are not implemented variously for reasons of funding, lack of local support, lack of entrepreneurialism by the municipality and lack of ability to implement because of capacity issues. Potential state assets which could bolster tourism and local development outcomes are not being realized and in many cases the assets themselves are in a state of deterioration because of neglect.